Roszczenie współwłaściciela o zwrot wydatków poniesionych w związku z rzeczą wspólną: [Claim of co-owner for reimbursement of expenses associated with common property] (Studia Prawnicze / The Legal Studies, 2011)
Kwestie dotyczące zwrotu wydatków poczynionych na rzecz wspólną stanowią jedno z podstawowych źródeł sporów powstających między współwłaścicielami rzeczy, o czym przekonuje w szczególności szereg wydanych w ostatnich latach orzeczeń Sądu Najwyższego dotyczących tychże zagadnień. Znaczna liczba sporów między współwłaścicielami, których przedmiotem są zasady zwrotu wydatków poniesionych na rzecz wspólną, wynika zapewne w dużej mierze z lakoniczności regulacji ustawowej dotyczącej tejże materii. Artykuł niniejszy stanowi próbę omówienia podstawowych elementów konstrukcji prawnej roszczenia współwłaściciela o zwrot wydatków związanych z rzeczą wspólną. This study is devoted to the analysis of the legal basis, the premises and the content of mutual claims of co-owners for reimbursement of expenses associated with common property, as it is regulated in Polish law. The author expresses the view according to which in Polish law the above mentioned obligation of co-owner is a special case of the general duty to reverse unjust enrichment, based on Article 405 of the Polish Civil Code. This opinion is opposed to the standard view according to which the obligation to pay compensation for expenses associated with common property is based only on Article 207 of the Civil Code. The view according to which the obligation to pay compensation for expenses associated with common property is a special case of the general duty to reverse unjust enrichment makes it possible to justify widely shared assumption that only expenses beneficial to all co-owners should be compensated for. Such expenses include costs incurred in order to improve the common property as well as costs incurred in order to avoid deterioration or loss of the common property. On the other hand, co-owners are not obliged to reimburse for expenses made only in order to satisfy subjective preferences of one of them. The author also argues that on the basis of the statutory regulations concerning unjust enrichment it is reasonable to differentiate between the content of claim for reimbursement of necessary expenses associated with the common property and the content of claim for compensation of improvements made by co-owner. As far as necessary expenses incurred by one of the co-owners are concerned, the obligation of the rest of the coowners is only monetary. On the other hand, if one of the co-owners incurred costs in order to improve the common property and these improvements are significant the co-owner may claim such improvements “in nature”, which means that the co-ownership is dissolved and the object of the common property is granted to the co-owner who made these improvements. In such a case other co-owners obtain amount of money which equals the value of their shares in the common property estimated without taking into account the value of improvements. However, the author also discusses the special cases when the improvements of the common property cannot be compensated “in nature”. In the final part of the study it is argued that the right to reimbursement for expenses incurred by the co-owner is transferred to a person who acquires share of this co-owner in the common property through contract only when there is explicit agreement to that effect or when the contractual transfer of the share is gratuitous.